O EMPREGO DA PGF2α COMO ESTRATÉGIA PARA REDUÇÃO DE PROCESSOS INFLAMATÓRIOS PÓS-PARTO EM PRIMÍPARAS PRECOCE DA RAÇA NELORE - MACHADO, João Victor Bezerra; MELO STERZA, Fabiana de Andrade; CORDEIRO, Dauydison Antônio Gonzalez; SILVA, Willian Aparecido Leite da; SILVA, Millena Vitória da; COSTA, Wallery Caroliny Costa da (ANAIS DO ENIC, 2025)
-